Music for special occasions - Handel, George Frideric 1685-1759; Sousa, John Philip 1854-1932; Lewis, Gary A.; Eddleman, David (Music magic video library, 1995)
In this video, viewers discover that music plays a role in special events in most cultures. Examples are shown from the United States, the United Kingdom, Korea and South America.